Student Engagement in High-Performing Schools: Relationships to Mental and Physical Health. Issue 13 (December 2014) - Conner, Jerusha; Pope, Denise
This chapter examines how the three most common types of engagement found among adolescents attending high-performing high schools relate to indicators of mental and physical health.